Clinical Features of Right-Sided Infective Endocarditis Occurring in Non-Drug Users - Lee, Mi-Rae (The Korean Academy of Medical Sciences, 2014)
Right-sided infective endocarditis (RIE) occurs predominantly in intravenous drug users in western countries, and it has a relatively good prognosis. Clinical features and prognosis of RIE occurring in non-drug users are not well known. We investigated the clinical findings of RIE in non-drug users. We retrospectively reviewed 345 cases diagnosed with IE. Cases with RIE or left-sided infective endocarditis (LIE) defined by the vegetation site were included and cases having no vegetation or both-side vegetation were excluded. Clinical findings and in-hospital outcome of RIE were compared to those of LIE. Among the 245 cases, 39 (16%) cases had RIE and 206 (84%) cases had LIE. RIE patients were younger (40±19 yr vs 50±18 yr, P=0.004), and had a higher incidence of congenital heart disease (CHD) (36% vs 13%, P<0.001) and central venous catheter (CVC) (21% vs 4%, P=0.001) compared to LIE patients. A large vegetation was more common in RIE (33% vs 9%, P<0.001). Staphylococcus aureus was the most common cause of RIE, while Streptococcus viridans were the most common cause of LIE. In-hospital mortality and cardiac surgery were not different between the two groups. CHD and use of CVC were common in non-drug users with RIE. The short-term clinical outcome of RIE is not different from that of LIE. GRAPHICAL ABSTRACT: [Image: see text]